Landscape Paintings of Painters: Participation Approach: Exploring the Varied Expressions of Landscape Paintings and their Influence on Indian Culture (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Landscape painting is exceptionally intriguing in spite of the fact that it has no deliberate history. There are divider paintings in Egyptian tombs and in Rome, Which can be classified as landscape paintings since they speak to rocks, plants and trees in their natural form. We may say that landscape Painting in Europe was an impossible to miss invention of the renaissance. The landscape components were bit by bit permitted to predominant this episode displayed in a painting. Rabindara Nath Tagore's writings are an unending storage facility of landscape images both visual and audio-related. Not just the assortment of landscape pictures found in his writings are stunning, the extensive variety of utilizations to which they have been put is amazing in their assorted qualities. Indian landscape takes birth in a playground of emotions in pain, preference, craving and trust, in the delights of straightforward living and the constancy and energy of lives are rhythm, tempered by scholarly reverberations of an once brilliant human progress.